A narrow bridge to life : Jewish forced labor and survival in the Gross-Rosen Camp system, 1940 - 1945 - Guṭerman, Belah 1942- (Berghahn Books, 2008)
Forced labor in Nazi Germany and the Nazi-occupied areas -- The forced-labor system in eastern upper Silesia: the establishment of organization Schmelt (1940-1944) -- Forced-labor camps for Jews in lower Silesia and the Sudetenland (1940-1944) -- Phases in the development of the Gross-Rosen main camp (May 1940-October 1943) -- The first subcamps of Gross-Rosen -- Deploying the network of camps -- Labor camps in the Sudetenland -- Code riese: the Führer's secret operation in the Eulen mountains -- Administration of the Gross-rosen labor-camp complex -- Survival in the Gross-Rosen labor camps -- Women in the Gross-Rosen labor camps -- Cultural and spiritual life in the Gross-Rosen labor camps -- The last to be liberated -- Liberation -- Concluding remarks